2019
DOI: 10.1155/2019/7353420
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Inflammation in Obesity-Psoriatic Patients

Abstract: Psoriasis is a common chronic inflammatory multisystemic disease with a complex pathogenesis consisting of genetic, immunological, and environmental components. It is associated with a number of comorbidities, including diabetes, metabolic syndrome, obesity, and myocardial infarction. In addition, the severity of psoriasis seems to be related to the severity of obesity. Patients with higher levels of obesity show poorer response to systemic treatments of psoriasis. Several studies have demonstrated that white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 89 publications
1
46
0
4
Order By: Relevance
“…Proinflammatory molecules released during chronic inflammation are implicated in certain co-morbidities, such as obesity, hypertension, diabetes mellitus, cardiovascular disease and depression. Paradoxically, epidemiologic evidence infers that obesity, via pro-inflammatory pathways, predisposes to both development and progression of psoriasis [4]. This association is shared with metabolic syndrome (MetS), not least the increased prevalence of cardiovascular risk factors and the ensuing cardiovascular morbidity [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory molecules released during chronic inflammation are implicated in certain co-morbidities, such as obesity, hypertension, diabetes mellitus, cardiovascular disease and depression. Paradoxically, epidemiologic evidence infers that obesity, via pro-inflammatory pathways, predisposes to both development and progression of psoriasis [4]. This association is shared with metabolic syndrome (MetS), not least the increased prevalence of cardiovascular risk factors and the ensuing cardiovascular morbidity [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that adipokines, such as leptin, adiponectin and resistin, produced by adipocytes and dysregulated in obesity and MetS, are the linchpins of this metabolic association and the so called 'psoriatic march': a concept of how severe psoriasis can drive cardiovascular comorbidity [10]. They have been shown to contribute independently to the adverse cardiovascular outcomes in patients with PsO and can be viewed as biomarkers of obesity-related inflammation and cardiovascular risk [4]. With this is mind, one should consider adipose tissue as an endocrine organ that has the capabilities, through local and systemic factors, to induce a low-level inflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…The average BMI of psoriasis patients is reported to be higher than the BMI of the general population [21]. One meta-analysis conducted on 35 studies exploring the relationship between BMI and psoriasis reported that on average, psoriasis patients have a BMI 1.26 kg/ m 2 greater than adults and 1.55 kg/m 2 greater than children (5-18 years old) without psoriasis [22]. Among the five factors analyzed, only obesity was found to have a significant positive association with LTR.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is a widely used indicator of systemic inflammation ( 6 ). High serum CRP levels have been reported in patients with active psoriasis and chronic plaque psoriasis ( 2 ). Serum CRP levels and complete blood count-derived biomarkers, such as NL and PL, have been associated with disease severity and joint involvement in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%